A trend analysis of Sars-Cov-2 anti-nucleocapsid IgG antibodies with a recommendation of the cut-off classification to identify naïve, vaccinated, and infected cases - Uysal, Serhat; Demirdağ, Kutbeddin Demirdağ; Batur, Mesut; Balın, Şafak Özer; Aşan, Mehmet Ali; Tartar, Ayşe Sağmak; Akbulut, Ayhan (My University, 2022)
Determination of the vaccination’s effect on immune responses with the emergence of the Sars-Cov-2 pandemic become an important issue. This study aimed to evaluate the response of the anti-nucleocapsid IgG (anti-N IgG) index in naïve, vaccinated, or infected cases, in addition to suggesting ‘How to distinguish between vaccinated versus infected cases via anti-N IgG?’. Anti-N levels of the naïve [0.03 (0.02–0.06)], vaccinated [0.7 (0.2–1.96)], and infected [3.07 (1.44–5.2)] groups were statistically different (p<0.0001). Anti-N levels were statistically different in all periods of the infected and vaccinated sub-groups (p<0.0001). An inter-group analysis of the cases with repeated tests established that there was no difference between the not-vaccinated (-1.44±1.27) and after-infection early-vaccinated (-1.62±0.93) groups (p=0.717). A significant difference was observed between the after-infection early-vaccinated (-1.62±0.93) and late-vaccinated groups (1.5±1.61) (p<0.0001). Three-category cut-off levels were calculated for the naive, vaccinated, and infected cases as ?0.32, 0.32–1.40, and ?1.40 respectively. The area under the receiver operating curve (AUROC) of this classification was 0.907 (95% CI, 0.879–0.930) and the AUROC of the manufacturer's cut-off (?1.40) was 0.790 (95% CI, 0.754–0.823) (p<0.0001). This study demonstrates that early vaccination after the infection does not affect the trend of the anti-N level. The manufacturers should set out to update their tests dating back to the pre-vaccine period for the post-vaccine period.
Keywords: Biyoloji; Mikrobiyoloji; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Biyokimya ve Moleküler Biyoloji